2019 ESC Guidelines for the management of patients with supraventricular tachycardia - article Editorial (Российский кардиологический журнал)
The Task Force for the management of patients with supraventricular tachycardia of the European Society of Cardiology (ESC)Developed in collaboration with the Association for European Paediatric and Congenital Cardiology (AEPC)